The Role of Branding in Attracting Customers via Influencers A Study of Iraqi Tourism Companies - Ismail Mahmoud, Basheer; Yahya Hadi, Mohammed; Abbas Doori, Yasmin Khudair (International Journal of Indonesian Business Review, 2025)
Purpose – According to the difference in the strength of the brand and the extent of its acceptance in the markets on which the company relies on developing its trademark and increasing its impact in the targeted markets. The company's ability to entice customers is determined, and one of the mechanisms that some companies follow is investing in influential people to increase the acceptance and dissemination of the brand. This study aims to measure the direct impact of the brand in attracting customers and indirect influence through the mediation of the use of influencers. Methodology/approach – an electronic questionnaire was used as main instructions to collect data of Iraqi tourism companies in the capital, Baghdad, and the sample size (396) respondents. and the study approach is the descriptive analytical study Findings – The brand of banks affect the attraction of customers, and the effect increases with the presence of the intermediate role of influencers. Novelty/value – This research explores the impact of branding on customer attraction through influencers in Iraq's tourism sector, an underexplored area. It fills a gap by analyzing how brand identity enhances influencer marketing effectiveness, offering practical insights for tourism companies to strengthen market positioning.